1993
DOI: 10.1002/rcm.1290071017
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the complexation of amino acids and peptides with β‐cyciodextrin using electrospray ionization mass spectrometry

Abstract: The formation of non-covalently bound inclusion complexes between p-cyclodextrin and peptides containing aromatic acid residues has been confirmed by electrospray ionization mass spectrometry. This preliminary study has indicated that phenylalanine and tryptophan residues can form 1 : 1 complexes with fi-cyclodextrin whereas no evidence for such a complex could be found for tyrosine residues. Bradykinin, which contains two phenylalanine residues, formed both 1 : 1 and 1 : 2 complexes.6-Cyclodextrin (p-CD) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 8 publications
0
36
0
1
Order By: Relevance
“…The net reaction is the replacement of the amino acid by the alkylamine in the cavity of ␤-CD* resulting in a gas-phase guestexchange reaction. The interactions of the guest molecule with the hydrophobic cavity and the hydrophilic rim of CD are known to play important roles in stabilizing the charge on the protonated amino acid [11,17]. The intermolecular hydrogen bonding interaction between the hydroxyl groups in the CD ring and the positive charge on the amino acid result in very stable complexes.…”
mentioning
confidence: 99%
“…The net reaction is the replacement of the amino acid by the alkylamine in the cavity of ␤-CD* resulting in a gas-phase guestexchange reaction. The interactions of the guest molecule with the hydrophobic cavity and the hydrophilic rim of CD are known to play important roles in stabilizing the charge on the protonated amino acid [11,17]. The intermolecular hydrogen bonding interaction between the hydroxyl groups in the CD ring and the positive charge on the amino acid result in very stable complexes.…”
mentioning
confidence: 99%
“…Various studies of noncovalent complexes between ␤-cyclodextrins and aromatic molecules have shown that the complexes that were known to be present in solution could be detected by ES-MS [11][12][13][14][15][16][17]. In all these studies, the aromatic guest molecules were bearing at least one polar group.…”
mentioning
confidence: 99%
“…However, the signal intensity was too low to perform MS/MS experiments, which, together with the lack of isotopic resolution, prevented us from unambiguously assigning these peaks. Given that the concentration of analytes in this control experiment was quite high (~100 μM), the presence of these small peaks in the mass spectrum is more consistent with the non-specific association of RuCD2 and cationized CDs in the ESI plume rather than with non-specific complexation between the CDs and ligand 2 in solution [31,43].…”
Section: Stoichiometry Of Complexesmentioning
confidence: 62%
“…A number of studies report on more or less successful analyses of noncovalent complexes where hydrophobic forces are considered to play a dominant role for the stability [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Liu et al [19,20] showed the preservation of hydrophobically stabilized complex between bovine β-lactoglobulin and its natural ligands, fatty acids, for the fraction of ESI-generated ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation